Serbian Version of the eHealth Literacy Questionnaire (eHLQ): Translation, Cultural Adaptation, and Validation Study Among Primary Health Care Users - Branko Vujkovic; Voin Brkovic; Ana Pajičić; Vedrana Pavlovic; Dejana Stanisavljevic; Dušanka Krajnović; Aleksandra Jovic Vranes (JMIR Publications, 2024)
BackgroundAs digital health services are increasingly developing and becoming more interactive in Serbia, a comprehensive instrument for measuring eHealth literacy (EHL) is needed. ObjectiveThis study aimed to translate, culturally adapt, and investigate the psychometric properties of the Serbian version of the eHealth Literacy Questionnaire (eHLQ); to evaluate EHL in the population of primary health care (PHC) users in Serbia; and to explore factors associated with their EHL. MethodsThe validation study was conducted in 8 PHC centers in the territory of the Mačva district in Western Serbia. A stratified sampling method was used to obtain a representative sample. The Translation Integrity Procedure was followed to adapt the questionnaire to the Serbian language. The psychometric properties of the Serbian version of the eHLQ were analyzed through the examination of factorial structure, internal consistency, and test-retest reliability. Descriptive statistics were calculated to determine participant characteristics. Differences between groups were tested by the 2-tailed Students t test and ANOVA. Univariable and multivariable linear regression analyses were used to determine factors related to EHL. ResultsA total of 475 PHC users were enrolled. The mean age was 51.0 (SD 17.3; range 19-94) years, and most participants were female (328/475, 69.1%). Confirmatory factor analysis validated the 7-factor structure of the questionnaire. Values for incremental fit index (0.96) and comparative fit index (0.95) were above the cutoff of ≥0.95. The root mean square error of approximation value of 0.05 was below the suggested value of ≤0.06. Cronbach α of the entire scale was 0.95, indicating excellent scale reliability, with Cronbach α ranging from 0.81 to 0.90 for domains. The intraclass correlation coefficient ranged from 0.63 to 0.82, indicating moderate to good test-retest reliability. The highest EHL mean scores were obtained for the understanding of health concepts and language (mean 2.86, SD 0.32) and feel safe and in control (mean 2.89, SD 0.33) domains. Statistically significant differences (all P<.05) for all 7 eHLQ scores were observed for age, education, perceived material status, perceived health status, searching for health information on the internet, and occupation (except domain 4). In multivariable regression models, searching for health information on the internet and being aged younger than 65 years were associated with higher values of all domain scores except the domain feel safe and in control for variable age. ConclusionsThis study demonstrates that the Serbian version of the eHLQ can be a useful tool in the measurement of EHL and in the planning of digital health interventions at the population and individual level due to its strong psychometric properties in the Serbian context.